Research on the Lattice Matching of Different Solute Atoms in BCC Fe: A Molecular Dynamics Simulation. Issue 6 (28th January 2022) - Wu, Minghui; Zhang, Xiaoxun; Ma, Fang; Li, Jiayi; Tian, Wenqi; Gongcheng, Meiqi; Xu, Luyang; Chang, Gaoyuan; Zhang, Cheng
Abstract: In this article, molecular dynamics simulation is used to primarily explore the lattice matching problem of solute atoms in different configurations after entering the Fe lattice at 0 K temperature. It reveals that by changing the initial configurations, metal solute atoms (Cr, Cu, Ti, Al) are more stable in the <110> configuration while C atom tends to stay in the octahedral gap of the BCC lattice. In addition, the matching mechanisms of different solute atoms in BCC Fe lattice in different configurations are elaborated in detail. The relaxation of metal solute atoms in different configurations eventually forms different stable structures while C atoms only exist in the nearest‐neighbor octahedral gap of the BCC Fe lattice in each configuration. Abstract : This work focuses on the lattice matching mechanism under different initial configurations and analyzes the relaxation evolution of each solute atom in the BCC Fe lattice. The results show that some metal atoms and Fe atoms are relatively stable in the <110> lattice configuration, while C atoms are in the octahedral gap.